Pengaruh Pelayanan Fiskus, Kesadaran Wajib Pajak, Pengetahuan Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Kabupaten Sidenreng Rappang - Andi Sri Kumala Putri P; Ari Ayu; Romy Nugraha JS (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to examine the effect of deferred tax expense, ownership concentration and sales volatility on earnings persistence in property & real estate companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The sample used is purposive sampling method, namely the method of selecting samples based on certain criteria. This type of research is quantitative using associative methods sourced from secondary data in the form of annual financial reports from the official website of the Indonesia Stock Exchange idx.co.id. The sample used is 10 property & real estate companies listed on the Indonesia Stock Exchange in 2017 to 2021. The analysis technique used is panel data regression analysis with the help of the Eviews 9 program. The results of this study indicate that the Deferred Tax Burden effect on Earning Persistence. Ownership concentration has no effect on Earning Persistence. Sales Volatility affects Earning Persistence. Deferred Tax Expenses, Concentration of Ownership and Sales Volatility affect Income Persistence.